Beliefs and attitudes of religious consumption in young people from Hidalgo, Mexico - Meneses Armenta, Omar Daniel (Mercados y Negocios, 2021)
The article aims to know what young people believe in and what consumer attitudes they take toward religious organizations in Hidalgo, Mexico. Descriptive research was developed with a survey with a Likert scale, interval, and proportion to 383 young people from the Autonomous University of the State of Hidalgo. The main result is that depending on the religion, they tend to be more dedicated to it and that the generations have created changes. The conclusion is that, unlike Catholicism, young people of other religions show greater focus. However, the generational change affects the interest in religion in a decreasing way, also affecting consumption for religious reasons. Not only in religion but also in other products or services, brand loyalty is fragile.